Profile of Contralateral Patent Processus Vaginali in Pediatric Patients with Unilateral Inguinal Hernia (Indian Journal of Forensic Medicine & Toxicology, 2020)
Objective: Reporting the incidence of contralateral patent processus vaginali (CPPV) in pediatric patientswith unilateral inguinal hernia. Methods: The study was conducted from November 2010 - February2012. Patient’s identity were recorded for registration number, name, age, gender, address and date ofexamination. The surgery was conducted by a trainee pediatric surgeon as a researcher and resident. Highligation procedure and diagnostic of contralateral PPV. Results: This study included 40 pediatric patients ofvarious ages diagnosed with lateral inguinal hernia. There were 31 male patients (77.5%), 24 patients (60%)with right inguinal hernia patients, and 14 patients (35%) aged 0-1 years. Conclusion: The transinguinallaparoscopic contralateral PPV technique is helpful in diagnosing the presence of contralateral PPV. Theincidence of contralateral PPV in this study was 27.5%. Furthermore, early age increased the incidence ofcontralateral PPV.